Microsatellite and inter-microsatellite markers linked with resistance to vascular streak dieback in cocoa (Theobroma cacao L.). Issue 3 (3rd May 2020) - Chandrakant, Ekatpure Sachin; Tulshiram, Waghmare Sandesh; Mathew, Deepu; Minimol, J. S.; Jose, Sherin; Kurian, Sainamole P.; Shylaja, M. R.
ABSTRACT: Vascular streak dieback is a serious disease of cocoa throughout the world and breeding of resistant varieties is the most reliable management strategy. Molecular markers linked with resistance enable marker-assisted breeding by tracking the resistance genes in each generation. To identify the markers linked with resistance, four accessions each of highly resistant, highly susceptible and partially resistant categories were screened with ISSR and SSR primers. Of the 71 ISSR and 46 SSR primers used, five ISSR primers UBC811, UBC815, UBC826, UBC857 and UBC866 have yielded reproducible markers for resistance. Cloning and sequencing of UBC857 marker showed 94% identity with SSR clone mTcCIR42. Screening of genotypes with mTcCIR42 primers generated distinct markers for resistance. Identified ISSR markers represent at least three different genes. Results were further validated using the resistant and susceptible progenies and are being used in marker-assisted selection for VSD resistance in cocoa.